2012
DOI: 10.1002/pen.23397
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of elastic constants of polymer/nanoparticles composites using the brillouin spectroscopy and the mechanical homogenization modeling

Abstract: A numerical model using homogenization techniques is proposed to simulate the evolution of elastic properties of nanocomposite polymer‐nanoparticles, depending on the concentration of nanoparticles and the rigidity of the particle–matrix interface. To validate this model, it was confronted to several physical systems having different interface behavior, the nanocomposite systems: poly(vinylidene fluoride trifluoroethylene)/Al2O3 (alumina nanoparticles incorporated into copolymer of vinylidene difluoride and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In the work carried out by Manapat et al [16], it was also observed that the increase in GO content resulted in a decrease in the mechanical strength, which they attributed to higher concentration of GO leading to excessive interplatelet interaction instead of GO-resin hydrogen bonding, thus decreasing GO-resin interaction, as well as the fact that the presence of GO in the resin can lower the efficiency of photopolymerization because the filler can serve as a barrier or hindrance to incoming laser light [16]. This observation was also similar to the case of carbon nanotube reinforced poly(methyl methacrylate) [23] and the GO containing PEGDA [20], respectively. Another possible explanation offered by Manapat et al [16] is that GO is acting as a chain transfer agent, which inhibits the further growth of polymer chain.…”
Section: Resultsmentioning
confidence: 69%
“…In the work carried out by Manapat et al [16], it was also observed that the increase in GO content resulted in a decrease in the mechanical strength, which they attributed to higher concentration of GO leading to excessive interplatelet interaction instead of GO-resin hydrogen bonding, thus decreasing GO-resin interaction, as well as the fact that the presence of GO in the resin can lower the efficiency of photopolymerization because the filler can serve as a barrier or hindrance to incoming laser light [16]. This observation was also similar to the case of carbon nanotube reinforced poly(methyl methacrylate) [23] and the GO containing PEGDA [20], respectively. Another possible explanation offered by Manapat et al [16] is that GO is acting as a chain transfer agent, which inhibits the further growth of polymer chain.…”
Section: Resultsmentioning
confidence: 69%
“…To explain the above‐mentioned impairment of the mechanical behavior, we tentatively consider a crucial importance of the parameters of the fibrils and the interface . The interface may be influenced by different crystalline‐phase content (including the amorphous layer), its orientation, and type.…”
Section: Resultsmentioning
confidence: 99%
“…The crucial role of the interface modulus was also demonstrated in nanocomposites . In this respect, of importance is the fact that the modulus of amorphous polyethylene (PE) is similar to that of elastomers, that is, with a value of several megapascals.…”
Section: Introductionmentioning
confidence: 99%